Revolutionizing Solar Energy with AI-Driven Enhancements in Photovoltaic Technology - Mohammad, Ashif; Mahjabeen, Farhana (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The important contribution of artificial intelligence (AI) to improving solar cell performance and its effects on sustainability and the integration of renewable energy. The article covers a wide range of AI-driven breakthroughs in solar energy, including material research and development, predictive models and control systems, manufacturing and deployment issues, and the application of big data analytics. It also looks into how artificial intelligence (AI) and machine learning algorithms may be used to increase solar cell efficiency, maximize energy production, and enable intelligent grid integration. The application of AI-driven algorithms for solar cell material design and development is the main topic of the first section. It demonstrates how AI has the potential to speed up the discovery and optimization of materials with improved stability and efficiency. In order to develop solar cell technologies, it also investigates how AI can be combined with nanotechnology, quantum computing, and machine vision. The use of AI-powered control systems and predictive models for monitoring and maintaining solar cell performance is covered in the second section. In order to enable effective grid integration and raise the overall reliability of solar energy systems, it highlights the role played by AI algorithms in spotting abnormalities, forecasting energy consumption, and optimizing energy generation. The final segment discusses the difficulties in producing and deploying solar cells as well as potential solutions based on AI. It highlights how AI may help improve system design, make site selection easier, and increase the sustainability of solar energy infrastructure. The fourth portion looks into how big data analytics might help solar energy reach its full potential. In order to maximize the use of solar energy and improve overall system efficiency, it investigates how AI algorithms can evaluate big datasets, optimize energy output, enable demand-side management, and encourage intelligent grid integration. The following sections delve into the specific subjects of machine learning algorithms, predictive models, and control systems for solar cell material design and development, AI-based solutions for monitoring and maintaining solar cell performance, AI-driven innovations in solar cell manufacturing and deployment, and the function of big data analytics in maximizing the efficiency of solar energy. The disruptive potential of AI in the solar energy sector is highlighted in each section, which covers the most recent developments, prospective effects, and future directions in various fields. Demonstrates the importance of AI-driven improvements in solar cell performance and their effects on the integration and sustainability of renewable energy sources. It emphasizes the potential of AI to accelerate the transition to a clean and sustainable energy future by optimizing energy production, expanding grid integration, increasing system efficiency, and more. The report highlights the necessity of ongoing research and development in AI technologies to fully realize the seemingly limitless potential of AI in solar energy and hasten the adoption of renewable energy sources around the world.